Efektivitas Model Project Based Learning (PJBL) Berbasis Youtube Channel Terhadap Hasil Belajar Dan Kemandirian Mahasiswa Pada Materi Fisiologi Tumbuhan - Jalil, Muhamad; Aprilia, Clarisa Ayu; Farihatunni’mah, Ananda; Triana, Bella Maya; Wahyuni, Silviani Indah (Bioeducation Journal, 2024)
Online learning often makes students feel bored quickly because they are monotonous in front of a laptop screen. The purpose of this study was to determine the effectiveness of implementing a project based learning (PJBL) model in the form of a clipping book based on a YouTube channel on student learning outcomes and independence in the plant physiology course. The design of this research is a one-shot case study. The research was conducted in September-December 2021. The research sample consisted of classes A5TBR and B5TBR, totaling 71 students. The research data is in the form of learning outcomes (NIPURA) for the plant physiology course and student independence. The technique of making Youtube videos is assisted by Microsoft Powerpoint 2007 and VLV media player. Learning outcomes were analyzed using one sample t test, while independence data was in the form of a Likert scale which was analyzed descriptively by percentage. The results of this study indicate that t arithmetic > t table (18.458 > 1.994) or Ho is rejected. Thus, the average value of student learning outcomes is not the same as the value of the comparison indicator (KKM=75). Student independence after implementing the PjBL model based on Youtube Channel got 59.09% in the very high category, 38.64% in the high category, and 2.27% in the low category. Indicators of each independence: (1) independence from others (very high), (2) self-confidence (high), (3) discipline (very high), (4) have a sense of responsibility (high), (5) self-initiative (high), and (6) self-control (very high). Aspects of independence that need to be improved from students are the responsibility and confidence of students during lectures.